Ubiquitous cold and massive filaments in brightest cluster galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Olivares, Valeria; Salomé, Philippe
Abstract: The origin of the mysterious multiphase filamentary structures surrounding Brightest Cluster Galaxies (BCGs) remains unknown. We present Atacama Large Millimeter/submillimeter Array (ALMA) and Multi Unit Spectroscopic Explorer (MUSE) observations for a sample of 15 BCGs to investigate the origin and life-cycle of the gas. Those observations show clumpy and massive molecular filaments, preferentially located around the radio bubbles inflated by the active galactic nuclei (AGN). We investigate where the cold gas condenses from the intra-cluster medium, by comparing the radial extent of the filaments with predictions from numerical simulations.